2020
DOI: 10.1038/s12276-020-00536-0
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Wnt5a-modified NSCs promotes tissue repair and locomotor functional recovery after spinal cord injury

Abstract: Traditional therapeutic strategies for spinal cord injury (SCI) are insufficient to repair locomotor function because of the failure of axonal reconnection and neuronal regeneration in the injured central nervous system (CNS). Neural stem cell (NSC) transplantation has been considered a potential strategy and is generally feasible for repairing the neural circuit after SCI; however, the most formidable problem is that the neuronal differentiation rate of NSCs is quite limited. Therefore, it is essential to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Jang et al discovered that Wnt5a could activate neural differentiation by activating the Wnt5a/JNK pathway [ 23 ]. Li et al also found that Wnt5a could promote NSC differentiation into neurons and further revealed that Wnt5a upregulated miRNA200b-3p expression through MAPK/JNK signaling, which was in accordance with our study [ 24 ]. In our study, we demonstrated that the expression of Wnt5a and p-JNK increased significantly during the differentiation of sp-NSPCs after LINGO-1 shRNA treatment, whereas the canonical Wnt pathway factor β-catenin did not change.…”
Section: Discussionsupporting
confidence: 93%
“…Jang et al discovered that Wnt5a could activate neural differentiation by activating the Wnt5a/JNK pathway [ 23 ]. Li et al also found that Wnt5a could promote NSC differentiation into neurons and further revealed that Wnt5a upregulated miRNA200b-3p expression through MAPK/JNK signaling, which was in accordance with our study [ 24 ]. In our study, we demonstrated that the expression of Wnt5a and p-JNK increased significantly during the differentiation of sp-NSPCs after LINGO-1 shRNA treatment, whereas the canonical Wnt pathway factor β-catenin did not change.…”
Section: Discussionsupporting
confidence: 93%
“…NSCs are isolated from the subventricular zone of the hippocampus of the brain and a region of the central canal of the spinal cord and can differentiate into specific neuronal or glial phenotypes to replace lost tissue or produce pro-regenerative factors. Transplantation of NSCs into the lesioned spinal cord leads to functional recovery, sustained through neuronal cell replacement that was able to reconstitute lost neuronal and glial tissue with trophic support (BDNF, CNTF, GDNF, NGF, and IGF-1) preserving damaged cells and axons [22]. Studies have shown the immunomodulatory activities of NSCs that can be helpful in the treatment of SCI [23].…”
Section: Neural Stem Cells (Nscs)mentioning
confidence: 99%
“…To elicit a SCEP, a single pulse stimulation (50 ms in duration at a frequency of 5.1 Hz and a voltage increase of 1 mV) was transmitted through the electrodes until a mild twitch of the vertebral body of the animal was observed. One hundred SCEP responses were averaged for each rat to obtain high-quality waveforms for the SCEP signals [32].…”
Section: Spinal Cord-evoked Potential (Scep) Recordingmentioning
confidence: 99%
“…To visualize the cavity area, animals (n = 5 per group) were killed for haematoxylin-eosin (HE) staining. The T8-T11 longitudinal spinal cord sections from each group were stained with HE according to standard protocols and observed under bright eld microscope [22,32].…”
Section: Histological Analysismentioning
confidence: 99%